2014
DOI: 10.1177/0363546514554769
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Tibial Tunnel Reaming on the Meniscal Roots During Cruciate Ligament Reconstruction in a Cadaveric Model, Part 1

Abstract: The ACL reconstruction tunnels reamed in the center of the ACL tibial footprint caused a significant decrease in the attachment area and ultimate strength of the AL meniscal root attachment. Clinically, repositioning guide pins placed in the lateral aspect of the ACL attachment before tibial tunnel reaming may minimize iatrogenic injuries to the AL meniscal root attachment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 34 publications
1
45
0
Order By: Relevance
“…These fibers specifically act on the LM anterior root attachment itself, explaining the reduction in the ultimate failure strength of the LM anterior root with disruption of these fibers. 7,19 Ellman et al 20 reported that the fibers overlying the ACL tibial insertion did not significantly modify the strength or the stiffness of the LM anterior root. Therefore, the LM extrusion identified in our study could have possibly resulted from damage to the fibers of the LM inserting into the subchondral bone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These fibers specifically act on the LM anterior root attachment itself, explaining the reduction in the ultimate failure strength of the LM anterior root with disruption of these fibers. 7,19 Ellman et al 20 reported that the fibers overlying the ACL tibial insertion did not significantly modify the strength or the stiffness of the LM anterior root. Therefore, the LM extrusion identified in our study could have possibly resulted from damage to the fibers of the LM inserting into the subchondral bone.…”
Section: Discussionmentioning
confidence: 99%
“…18,28,33,34 Ziegler et al and Zantop et al reported this "true" center to be located 7.5 mm from the center of the LM anterior root. 2,18 However, LaPrade et al 7 suggested that the functional importance of the supplemental soft tissue fibers of the LM anterior root should be considered and suggested a location at 5.0 mm from the center of the LM anterior root. We agree with this latter recommendation.…”
Section: Location Of the Tibial Tunnelmentioning
confidence: 99%
See 2 more Smart Citations
“…This anteromedial injury might obfuscate the recognition of ALMR injury. Nevertheless, a number of cadaveric studies have indicated that anatomic single-bundle ACL reconstruction can significantly decrease ALMR attachment area and strength, as the native ACL tibial insertion is overlapped with the ALMR (Laprade et al 2014b; Watson et al 2015). Regarding the attachment area, some studies report that the ALMR is smaller than the anteromedial meniscal root (44.5 mm 2 vs 93 mm 2 ) (Johnson et al 1995; Kohn & Moreno 1995).…”
Section: Discussionmentioning
confidence: 99%